A multi-level meta-analysis of the relationship between decision-making during birth and postpartum mental health - Louisa Arnold; Marie Völkel; Jenny Rosendahl; Michael Rost (Health Psychology and Behavioral Medicine)
Introduction There is accumulating evidence of ineffective decision-making between birthing individuals and healthcare providers during childbirth. While research syntheses have demonstrated that negative birth experiences are associated with postpartum mental health, primary quantitative studies linking specific decision-making measures and mental health outcomes have not been synthesised. The present study aims to fill this gap in order to provide hands-on evidence on how to further improve perinatal care.Methods A systematic literature search using Bolean logic was conducted. A final set of 34 publications from 14 different countries could be included in our meta-analysis. Measures of intrapartum decision-making were consolidated into four key domains: information, respect, control, and involvement. We conducted multi-level meta-analyses to assess the overall relationship of intra-partum decision-making and mental-health outcomes, as well as the specific correlations associated with each decision-making domain.Results Our analysisrevealed that less effective intrapartum decision-making is associated with more postpartum overall mental health problems (r = -.25), depression (r = -.19), and posttraumatic stress disorder (r = -.29). More precisely, while all domains of intrapartum decision-making (information: r = -.22, involvement: r = -.23, respect: r = -.28, control: r = -.25) were associated with postpartum overall psychopathology, only information (r = -.18), respect (r = -.25), and control (r = -.12) were associated with depression, and only involvement (r = -.31), respect (r = -.32), and control (r = -.25) were associated with posttraumatic stress disorder. A higher percentange of planned cesarean sections in a sample and longer time lags between birth and post-effect measurement were identified as moderating variables.Conclusions Ineffective decision-making is a significant contributing factor to the development of adverse postpartum mental health problems outcomes. Implications for practice concern establishing numerous antenatal care contacts as a standard to enhance birth preparedness for both birthing individuals and providers. Additionally, measuring the experience of intrapartum decision-making as an indicator of quality of care as a default to monitor, analyse, and improve decision-making and to facilitate accountability systems.